Translating Czernowitz: The “Non-Place” of East Central Europe - Leslie Morris (Studies in 20th & 21st Century Literature, 2007)
The historian Karl Schlögel’s proclamation that Czernowitz is a “real place” and not just a literary topos serves as the point of departure, and the point of contention, for this essay. This essay examines the rhetorical and textual recreations of Czernowitz as “place” on contemporary maps of Jewish mourning and, specifically, in the work of the Czernowitz-born poet Rose Ausländer. Czernowitz poses an interesting problem for contemporary literary and cultural theory that seeks to map the fault lines between literary text, cultural and historical memory, and geographical and textual sites of memory. This legendary Jewish city, once a part of the Habsburg empire and now in Ukraine, is present as a textual site of memory, as the locus—even the embodiment—of the absence of Jewish culture in east Central Europe. This essay examines the literary and cultural meanings of Czernowitz, the layers of repetition and echo in the evocation of Czernowitz as place within the “non-place” of east Central Europe. In doing so, it sets out to define several new “tasks” for the literary “translation” of a place whose contours and boundaries have shifted in time, a place that is both heavily remembered and, at the same time, forgotten.
Keywords: Karl Schlögel; Czernowitz; translation; Jewish mourning; place; Rose Ausländer; poet; poetry; cultural theory; contemporary literature; literary text; cultural memory; historical memory; Habsburg; Autrian; Austria; Central Europe; Jewish culture; judaism